Describing Nonlinear RLC Circuit Equation Using Laplace Decomposition Method - Thunibat, Reem G.; Akour, Abdulrahman N.; Jaradat, Emad K.; Jaradat, Omar K. (Journal of Applied Nonlinear Dynamics, 2026)
In this article, the Laplace Adomian Decomposition Method (LADM) is developed to investigate an approximate solution of nonlinear RLC Circuit Equation. This technique involving a permutation between the Laplace transforms (LTM) method with the Adomian decomposition method (ADM). The nonlinear part is involved through an infinite series of Adomian polynomials, and the (LADM) gives an infinite series solution to the equation.